Pengadaan dan Pemasangan Panel Surya sebagai Sumber Energi Listrik Alternatif untuk Alat Otomatis Pencuci Tangan di Pasar Mitra Raya Kota Batam - Susanto Susanto; Ahmad Riyad Firdaus; Qoriatul Fitriyah; Hendawan Soebhakti; Arif Febriansyah Juwito; Senanjung Prayoga; Indra Hardian Mulyadi; Eka Mutia Lubis; Fitriyanti Nakul; Widya Rika Puspita; Ika Karlina Laila Nur Suciningtyas; Ridwan Ridwan; Juliansyah Yangu; Rabiah Al Adawiyah Anwar; Andi Hartanto; Ira Zamzami; Ilham Kurnia; Salman Alfarizi; Rogen Samuel Hasibuan (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
Washing hands is something that is always urged to be done lately. This pandemic makes washing hands a habit that must be accomplished before and after doing activities. Automatic hand washing is one way to reduce the spread of the virus because it can be used without having to touch the device directly. The development of automatic tools for washing hands is the crucial need for an alternative power source that is fuel-efficient and uncomplicated in terms of maintenance. The eco-friendly electrical source is needed to be implemented to reduce the electricity bills such as using the solar panel as the alternative power source. As an effort to support handwashing activities, the procurement of solar panels as a source of electrical energy is expected to be able to provide simple solutions to prevent the spread of Covid -19 and to make the environment clean and energy-efficient.